2001
DOI: 10.1556/aagr.49.2001.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Sowing Methods on Yield and Bulb Characteristics in Onion (Allium Cepa L.)

Abstract: Direct sowing (DS), row direct sowing (RDS), and the transplanting method (TM) were investigated for two onion cultivars, Azar-Shahr (red skin onion) and Horand (yellow-brown skin onion) during 1999, at Khalat-Pooshan Research Station, Tabriz University. Analysis of variance for the measured traits indicated that except for the percentage of class II onions, other traits were significantly influenced by the sowing methods. TM had higher values of total yield, marketable yield, percentage of class I and III, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
1
3
1
Order By: Relevance
“…In addition, very heterogeneous and under-sized bulbs were recorded with broadcasting method due to uneven spacing and maximum plant population per unit area. The similar results were also disclosed by Motallebi et al (2001) and Khokhar et al (1990). They reported that transplanting method produced more homogenous bulbs than that of direct seeding.…”
Section: Effect Of Planting Methods On the Yield And Quality Onionsupporting
confidence: 88%
See 4 more Smart Citations
“…In addition, very heterogeneous and under-sized bulbs were recorded with broadcasting method due to uneven spacing and maximum plant population per unit area. The similar results were also disclosed by Motallebi et al (2001) and Khokhar et al (1990). They reported that transplanting method produced more homogenous bulbs than that of direct seeding.…”
Section: Effect Of Planting Methods On the Yield And Quality Onionsupporting
confidence: 88%
“…Ahmed and Hassan (1978) reported that transplanting method delayed the maturity of bulbs. Ketema et al (2013) and Motallebi et al (2001) disagree with the present result. They stated that maturity was significantly more delayed in direct seeding method than that of transplant.…”
Section: Effect Of Planting Methods On the Growth And Maturity Of Onioncontrasting
confidence: 83%
See 3 more Smart Citations